Examining Relationships Between Groundwater Nitrate Concentrations in Drinking Water and Landscape Characteristics to Understand Health Risks. (2nd May 2022) - Hamlin, Q. F.; Martin, S. L.; Kendall, A. D.; Hyndman, D. W.
Abstract: Nitrate ingested from drinking water has been linked to adverse health outcomes (e.g., cancer, birth defects) at levels as low as ∼2 mg/L NO3 ‐N, far below the regulatory limits of 10 mg/L. In many areas, groundwater is a common drinking water source and may contain elevated nitrate, but limited data on the patterns and concentrations are available. Using an extensive regulatory data set of over 100, 000 nitrate drinking water well samples, we developed new maps of groundwater nitrate concentrations from 76, 724 wells in Michigan's Lower Peninsula, USA for the 2006–2015 period. Kriging, a geostatistical method, was used to interpolate concentrations and quantify probability of exceeding relevant thresholds (>0.4 [common detection limit], >2 mg/L NO3 ‐N). We summarized this probability in small watersheds (∼80 km 2 ) to identify correlated variables using the machine learning method classification and regression trees (CARTs). We found 79% of wells had concentrations below the detection limit in this analysis (<0.4 mg/L NO3 ‐N). In the shallow aquifer (focus of study), 13% of wells exceeded 2 mg/L NO3 ‐N and 2% exceeded the EPA maximum contaminant level of 10 mg/L. CART explained 40%–45% of variation in each model and identified three categories of critical correlated variables: source (high agricultural nitrogen inputs), vulnerable soil conditions (low soil organic carbon and high hydraulic conductivity), and transport mechanisms (high aquifer recharge). These findings add to the body of literature seeking to identify communities at risk of elevated nitrate and study associated adverse health outcomes. Plain Language Summary: High levels of nitrate ingested via drinking water can lead to a variety of adverse health outcomes, including blue baby syndrome at high levels (>10 mg/L NO3 ‐N), a variety of cancers, and birth defects at chronic lower levels (∼>2 mg/L NO3 ‐N). In agricultural areas, groundwater is often used for drinking water and can have elevated nitrate levels. In Michigan, USA, we used over 100, 000 samples from drinking water wells to map nitrate levels in groundwater in the 2006–2015 period. We found 2% of wells exceeded the EPA's maximum contaminant level of 10 mg/L NO3 ‐N and 13% exceeded 2 mg/L, a lower level recently associated with adverse health outcomes. We used a geostatistical method and machine learning algorithm to analyze potential landscape and geologic characteristics associated with nitrate. We found that higher nitrate levels were potentially driven by three factors: source (agricultural nitrogen inputs), vulnerable soils (low organic carbon content and soil permeability to water flow), and contaminant transport mechanisms (recharge, or the amount of water reaching groundwater). Mapping and analyzing this large data set improves our ability to identify populations at risk of elevated nitrate and provides a framework to improve effective nitrogen management. Key Points: Groundwater nitrate concentrations were mapped using over 100, 000 samples in Michigan's Lower Peninsula for 2006–2015 Concentrations were linked with a suite of potential driver variables using classification and regression trees Elevated nitrate was related to source (agricultural nitrogen inputs), vulnerability (soil conditions), and transport (aquifer recharge)